Use of chloroquine, azithromycin and ivermectin during the COVID-19 pandemic: An integrative review (Research, Society and Development, 2023)
During the COVID-19 pandemic, the scientific community vehemently searched for medicines that could help treat the disease in question. Medications such as chloroquine, azithromycin and ivermectin were used as self-medication, before confirming their effectiveness against the virus and the disease. After just over two years since the start of the global COVID pandemic, the way we take care of our health still raises hypotheses among the population about the different correct ways of dealing with the disease, stating that different approaches would be effective or not? The objective gathered evidence on the pharmacokinetics, proposed mechanism of action in COVID-19, adverse effects, efficacy and safety of chloroquine/hydroxychloroquine, azithromycin and ivermectin for prophylaxis and treatment of COVID-19. The methodology used was an integrative review, which followed the recommendations of the adapted PRISMA guideline. The literature search was conducted in the PubMed, LILACS and MEDLINE databases. A critical analysis was carried out to determine the methodological rigor of the studies, based on the assessment of the level of scientific evidence. The results showed that the use of hydroxychloroquine, chloroquine, azithromycin or ivermectin, in mild or severe forms of COVID-19, both in treatment and prophylaxis, did not demonstrate any benefit in reducing mortality, hospitalizations or other unfavorable outcomes, without limiting transmission. virus nor preventing the installation of infection. Concluding that the use of these aforementioned medications as prophylactic and therapeutic measures for COVID-19 is contraindicated, due to the lack of consistent favorable evidence and the numerous reports of adverse outcomes in such treatments.